PERCEPTIONS OF NURSES IN BASIC HEALTH UNITS REGARDING THEIR ACTIONS IN CASES OF DEPRESSION - Souza, Jéssica Kayane de; Mendes, Daniela do Carmo Oliveira; Silva, Grasiele Cristina Lucietto da; Vedana, Kelly Graziani Giacchero; Scorsolini-Comin, Fabio; Fiorati, Regina Célia; Ferreira, Luana Vieira Coelho (Cogitare Enfermagem, 2023)
Objective: To understand how nurses deal with depression in basic health units. Method: Qualitative research was carried out in 2020 through an open interview with 15 nurses working in basic health units in a municipality in the Brazilian Midwest region. The interviews were subjected to content analysis. Results: It was possible to see that nurses have multifactorial difficulties in dealing with cases of depression. However, they point out strategies that indicate ways to qualify their clinical practice, such as the importance of professional training and strengthening teamwork, so they are prepared and qualified to offer effective and humanized nursing care to people with depression. Conclusion: Even in the face of the challenges that have arisen, the continuity of nursing actions aimed at patients with depression and other mental disorders is fundamental, especially in contexts with a weakened mental health care network.